2019
DOI: 10.1186/s13063-019-3310-y
|View full text |Cite
|
Sign up to set email alerts
|

Video feedback intervention to enhance parental reflective functioning in primary caregivers of inpatient psychiatric children: protocol for a randomized feasibility trial

Abstract: Background Children requiring hospitalization for psychiatric care have serious disorders, high use of psychotropic medication, and frequent readmissions. The development and implementation of therapies focused on incorporating primary caregivers or attachment figures is necessary for working with children with severe psychiatric disorders. Mentalization or parental reflective functioning (PRF) is the ability of parents to understand their children’s behaviors as an expression of internal emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Parental RF enables parents to regulate their feelings and behaviors toward their child in the context of parent-child interactions (Fonagy et al, 2002;Leyton et al, 2019;Rostad & Whitaker, 2016). Four studies demonstrated the effect of parental RF-focused interventions on parent-child interaction in children <36 months.…”
Section: Do Parental Rf-focused Interventions Predict Parentchild Intmentioning
confidence: 99%
“…Parental RF enables parents to regulate their feelings and behaviors toward their child in the context of parent-child interactions (Fonagy et al, 2002;Leyton et al, 2019;Rostad & Whitaker, 2016). Four studies demonstrated the effect of parental RF-focused interventions on parent-child interaction in children <36 months.…”
Section: Do Parental Rf-focused Interventions Predict Parentchild Intmentioning
confidence: 99%
“…We observe that the pediatrician guidance might potentially sustain parents in shifting the attention from personal preoccupation towards the observation of infant competencies and initiatives. In this way, PC-VIT could modify both parents' subjective experience of a delicate moment and their interactive behaviors, making them more aware of their reactions and giving more realistic views of their child [29]. An enhanced ability to recognize infant autonomy and competences during relevant milestones, such as the weaning process, might be transferred into more sensitive and attuned daily interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches base the choice of each session theme upon the particular case [23][24][25][26][27][28].Video-feedback for supporting parenting can be used for simultaneous purposes: (i) To aid parents to better notice and identify children's cues; (ii) to recognize and perhaps change parental behaviors; (iii) to better hypothesize the motivational roots of the child's behaviors. Overall, parents' experience of observing themselves in the video aids achieving a more realistic perspective on their relationship with their child [29]. In particular, they become more aware of their own reactions and are supported in better hypothesizing the motivational roots behind the child's behaviors.…”
Section: Video-feedback Interventionsmentioning
confidence: 99%
“…The protocol describing the methods in detail was previously published (23), the trial was retrospectively registered on ClinicalTrials.gov NCT: 03374904. This feasibility trial is reported with the Consolidated Standards of Reporting Trials (CONSORT) guideline for pilot trials (24).…”
Section: Methodsmentioning
confidence: 99%